Pengolahan Abon Lele tanpa Minyak di Desa Buyut Ilir Kabupaten Lampung Tengah - Ikromatun Nafsiyah; Seftylia Diachanty; Siti Lestari; Nanda Syukerti (Jurnal Nusantara Mengabdi, 2023)
Purpose: This community service activity is aimed to optimalize the processing of fresh catfish and increase the knowledge, understanding, and ability of participants regarding the processing of catfish floss without oil as an alternative processing of fresh catfish, also obtain healthier fish floss. Methodology: This activities carried out through several stages, starts from the preparation, implementation, and evaluation stages. The method used is to provide some theory and practice online using Zoom Meeting. Catfish floss without oil is processed with several stages such as fish preparation, steaming, mashing, and roasting. Results: Participants know in theory the benefits, handling, and diversification of processed catfish, especially fish floss without oil. Participans can also practice directly processing fish floss without oil, thus creating opportunities for a home industry that specifically processes catfish cultivation in Buyut Ilir village. The processed products produced are expected to increase the consumption and economic conditions, especially Buyut Ilir village. Conclusion: Participants know in theory the benefits, handling, and diversification of processed catfish, especially fish floss without oil. Participants also practiced directly processing of fish floss without oil, thus creating opportunities for a home industry that specifically processes catfish cultivation in Buyut Ilir village. This community service activity also has increased the knowledge, understanding, and ability of participants regarding the processing of catfish floss without using oil as an alternative processing of fresh catfish and make healthier catfish floss.